Firian rising. vol. 01 - Stevens, Carly ((unknown location) : Self-published, 2019)
Strong-willed Firian Kess can create reality from his imagination, which earns him a spot in the elite Tanyuin Academy. His path collides with Kiria Arioc, spirited heir to a throne of the Western Kingdom, who, despite having abilities of her own, doubts her ability to lead. To succeed, they must navigate enemies, intrigue, and their own demons.
Keywords: Leaders -- Fiction; Supernatural abilities -- Fiction; Warriors -- Fiction; Fantasy fiction; Young adult fiction